Amphimermis enzoni n.sp. (Nematoda: Mermithidae) parasitizing dragonflies and damselflies in Argentina - Rusconi, José Matías (2020)
A mermithid nematode was found parasitizing nymphs of dragonflies and damselflies. The host specimens were collected from the stream Cajaravilla, Magdalena, Buenos Aires state, Argentina. In this work, we described Amphimermis enzoni n. sp., a nematode new to science. Nematodes were identified through morphological and molecular methods. The combination of the following characters separates A. enzoni n. sp. from other members of the genus Amphimermis Steiner: long and S-shaped vagina, twisted spicules for proximal 34% of their length, untwisted for 12%, again twisted for 30%, and untwisted for the last 24%; genital papillae arranged in three rows, medial row marginally longer than sub-medial rows; medial row bifurcated immediately anterior and posterior to cloaca, with 111 genital papillae (73 pre-anals and 38 post-anals). The sequences of 18S rDNA regions from A. enzoni formed a well-supported monophyletic clade with two GenBank sequences of Amphimermis spp. (EF617354 and EF617355) with 0.63 to 1.26% divergence and two Mermithidae spp. (LC512371 and LC512370) with 0.63 to 1.1% divergence, respectively. To our knowledge, this is the first example of mermithid infection in nymphs of dragonflies and damselflies for South America.